The Climate-system Historical Forecast Project: do stratosphere-resolving models make better seasonal climate predictions in boreal winter? - Butler, Amy H.; Arribas, Alberto; Athanassiadou, Maria; Baehr, Johanna; Calvo, Natalia; Charlton-Perez, Andrew; Déqué, Michel; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X; Fröhlich, Kristina; Hendon, Harry; Imada, Yukiko; et al. (Quarterly Journal of the Royal Meteorological Society, 2016)
ISSN:0035-9009 ISSN:1477-870X